2020
DOI: 10.3390/jcm9103214
|View full text |Cite
|
Sign up to set email alerts
|

CDK 4/6 Inhibition Overcomes Acquired and Inherent Resistance to PI3Kα Inhibition in Pre-Clinical Models of Head and Neck Squamous Cell Carcinoma

Abstract: Activating alterations in PIK3CA, the gene coding for the catalytic subunit of phosphoinositide-3-kinase (PI3K), are prevalent in head and neck squamous cell carcinoma (HNSCC) and thought to be one of the main drivers of these tumors. However, early clinical trials on PI3K inhibitors (PI3Ki) have been disappointing due to the limited durability of the activity of these drugs. To investigate the resistance mechanisms to PI3Ki and attempt to overcome them, we conducted a molecular-based study using both HNSCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Rubia philippinensis Elmer (Rubiaceae) is a rambling and low-climbing perennial plant and has rarely been investigated for its diverse chemical constituents and biological activities until the past decade. In a continuing initiative for the identification of bioactive secondary metabolites from R. philippinensis , we herein applied combinatorial applications of contemporary NMR-coupled computational protocols to elucidate the full structure of the new benzo­[ g ]­isochromene 1 bearing a flexible stereodiad, identified from the title plant. The configurational analysis was implemented via computational approaches such as DP4, direct J -DP4 (d J -DP4), and DP4 Plus with shielding tensors and coupling constants considered.…”
mentioning
confidence: 99%
“…Rubia philippinensis Elmer (Rubiaceae) is a rambling and low-climbing perennial plant and has rarely been investigated for its diverse chemical constituents and biological activities until the past decade. In a continuing initiative for the identification of bioactive secondary metabolites from R. philippinensis , we herein applied combinatorial applications of contemporary NMR-coupled computational protocols to elucidate the full structure of the new benzo­[ g ]­isochromene 1 bearing a flexible stereodiad, identified from the title plant. The configurational analysis was implemented via computational approaches such as DP4, direct J -DP4 (d J -DP4), and DP4 Plus with shielding tensors and coupling constants considered.…”
mentioning
confidence: 99%
“…Different molecular paths can lead to isiPI3K resistance, including sustained activation of mTORC1 [ 21 , 54 , 55 ], PDK1/SGK1 [ 56 ], and MYC [ 57 ]. In HNC HPV− , acquisition of resistance to isiPI3K is driven by increased activity of receptor tyrosine kinases (RTK), like EGFR [ 20 , 58 ], AXL [ 20 , 59 , 60 ], and HER3 [ 61 ], which signal through AKT or RAS/ERK pathways, or by activation of RTKs downstream of ERK/TSC2 [ 61 ], p85 [ 62 ], and CDK4/6 [ 63 ]. While, in HNC HPV− , different mechanisms of resistance to isiPI3K have been well documented by us and by others, in HNC HPV+ , only innate resistance to isiPI3K has been reported [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with excessive CDKs in HNSCC disclosed by the genomic studies, Remer et al reported that CDK4/6 inhibitors are effective to overcome acquired, inherent resistance to PI3Kα inhibition in pre-clinical models of HNSCC [ 27 ]. Besides, a CDK2 inhibitor could be another approach to target cancer drug resistance [ 12 ].…”
Section: Drug Resistancementioning
confidence: 98%